Evaluation of the NZAID Project - Freeman, Scarlet Lopez; Lee, Seung Bok; Ngo, Katrina; Vasudevan, Veena; Wu, Diana (Consilience, 2009)
Evaluation of “Institutionalizing Community–Based Integrated Watershed Management within Local Government Units in the Bicol Region, Philippines: Scaling Up and Sustaining Capacity–Building Outcomes at Local Level” for the IIRR BICOL Program